Effect of cognitive and executive functions on perception of quality of life of cognitively normal elderly people dwelling in residential aged care facilities in Sri Lanka - Gamage, M.W.K; Hewage, D.C; Pathirana, K. D. (BMC Geriatrics, 2018)
Background: Although cognitive functions affect the health related quality of life (QoL), the relationship between perceived QoL and cognition including executive functions has not been studied adequately. Available studies show moderate to weak correlations. We evaluated the association of cognition and executive functions, namely working memory (WM) and inhibitory control (IC) with the perceived QoL of a sample of elderly people dwelling in residential aged care facilities (RACFs) in Southern Province of Sri Lanka. Methods: Cognition was assessed using Mini-Mental State Examination (MMSE), while verbal WM (VWM), visuo-spatial WM (VSWM) and IC (interference control, inhibition of pre potent and ongoing responses) were assessed using VWM, VSWM tasks, colour word Stroop (CWS), go/no-go (GNG) and stop signal (SS) tasks respectively. WHOQoL-Bref (Total score and domain scores) were used to assess QoL. The relationship was analysed using Pearson correlation and hierarchical multiple regression analysis. Results: Study included 237 elderly people with a mean age of 71.11 ± 6.44 years. Participants scored the highest in the domain of environment (63.48 ± 10.63) and lowest in the domain of social relationships (55.43 ± 21.84) of QoL. Psychological health domain positively correlated with MMSE, VSWM and VWM scores and negatively correlated with CWS, SS and GNG task errors. Both physical health domain and total QoL demonstrated positive correlations with MMSE, VSWM and VWM scores, while negative correlations were observed with CWS task errors. Social relationships domain demonstrated a significant positive correlation with VSWM score. Environment domain positively correlated with MMSE, VSWM and VWM scores and negatively correlated with CWS and SS task errors. All were significant but weak correlations. When controlled for covariates, such as educational status, physical activity and marital status, cognition was a predictor of the domain of environment of QoL, while executive functions were not predictors of total QoL and domains of QoL. Conclusion: Cognition and executive functions weakly but significantly correlated with different domains of QoL. Only the level of cognition measured by MMSE was a predictor of the domain of environment of QoL and executive functions were not predictors of total QoL and domains of QoL in elderly people with normal cognitive functions dwelling in RACFs.
Keywords: Cognition, Working memory, Inhibitory control, Quality of life, Elderly